Recognition of prior learning: An elusive goal for the non-formal learner? - Thakrar, Jayshree Sona (My University, 2006)
Recognition of prior learning (RPL), the practice of valuing adults’ learning, derived from formal, informal or non-formal contexts, forms a key component of the transformational agenda of the education landscape in South Africa. Yet few institutions of higher education in South Africa practice RPL. The aim of this study is to provide insight into RPL by evaluating its current practice at one institution of higher education, the University of Fort Hare, highlighting its successes and challenges. The sources of information for this study included past RPL candidates, RPL assessors and co-ordinators, and the policy, processes and procedures that govern the RPL process in the institution. The methods used to collect the data included interviews, observation of institutional RPL workshops and an analysis of relevant RPL documentation. The research results suggest that there has been a limited uptake of RPL, which has impeded a holistic approach to RPL. Challenges include the draft status of an institutional policy, inconsistent RPL practices, the limitations of some of the RPL assessment methods, the lack of RPL data systems, the costs associated with supporting RPL candidates, the duplication of resources and practices, and the impact on academic workloads. A series of recommendations have been made to address these and other challenges highlighted in the research results.
Faculty of Humanities School of Education 0415279k jthakrar@ofh.ac.za
Keywords: RPL; Higher Education; Saouth Africa; Adult Education; SAQA